An empirical analysis of HRM practices and organisational performance relationship in the context of developing nation: The moderating effect of ethical climates - Sabiu, Malam Salihu; Tang, Swee Mei; Joarder, Mohd Hasanur Raihan (Society of Scientific Research and Education (SSRE), 2016)
The purpose of this study is to examine the moderating effect of ethical climates (ECs) on the relationship between HRM practices and organizational performance (OP).Based on the Resource Based View (RBV) perspective, HRM practices are the best internal resources influencing performance in organization.Some scholars used individual practice while others used bundles.Despite these studies, however, few studies have attempted to consider the influence of HRM practices on organizational performance. Even if any, they have reported mixed findings; therefore, a moderating variable is suggested.This paper proposes ethical climates (ECs) as potential moderator on the relationship between HRM practices and organizational performance to enhance the relationship.A quantitative survey method was used; the data were collected from the heads of department in selected ministry of education Nigeria. A total of 105 questionnaires administered, 81 questionnaires were collected. PLS SEM was used for the data analysis.Based on the statistical findings, recruitment and selection and training and development were found to be significantly related to organisation performance.While ethical climates found to moderate on the relationship between recruitment and selection and training and developments and OP. The study also suggested for future research.